1999
DOI: 10.1111/j.1755-6686.1999.tb00020.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure measurement in haemodialysis patients

Abstract: Several studies suggest that the 24 hour ambulatory blood pressure monitoring (ABPM) predicts left ventricular hypertrophy more accurately than conventional blood pressure measurement (CBPM) with mercury sphygmomanometer. We estimated the left ventricular mass by M-mode echocardiography in 58 patients on regular haemodialysis treatment during the midweek haemodialysis (HD) interval. ABPM was recorded during the 24 hours preceding the dialysis session and the average of values were compared with the average of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In studies in which the pre/postdialysis BP and ABP were reported separately for two groups (21)(22)(23)(24)(25), results were pooled by taking the square root of the weighted average of the variances. In two studies, the correlation coefficients between ABP and pre/ postdialysis BP but not the SD of the routine BP were reported (26,27). Data from these studies were used to calculate pooled correlation coefficients but not for calculating the weighted mean difference between BP.…”
Section: Resultsmentioning
confidence: 99%
“…In studies in which the pre/postdialysis BP and ABP were reported separately for two groups (21)(22)(23)(24)(25), results were pooled by taking the square root of the weighted average of the variances. In two studies, the correlation coefficients between ABP and pre/ postdialysis BP but not the SD of the routine BP were reported (26,27). Data from these studies were used to calculate pooled correlation coefficients but not for calculating the weighted mean difference between BP.…”
Section: Resultsmentioning
confidence: 99%